A New Unidimensional Family Resilience Scale in an Indonesian Context: Development and Psychometric Properties - Iqbal, Muhammad; Roebianto, Adiyo; Wardani, Laila Meiliyandrie Indah (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2025)
This study aims to develop a psychological instrument of family resilience using data derived from Indonesian samples based on a five-dimensional resilience scale: physical resilience, psychological resilience, economic resilience, social resilience, and religiosity resilience. Each dimension was measured with five items (25 items in total) on a 4-point Likert scale. A total of 841 subjects (n = 841) were gathered through purposive sampling and were required to complete the questionnaire. Data were analysed using confirmatory factor analysis (CFA) and Rasch analysis, aimed at generating each item’s validity based on the formulated constructs. Results indicated that all item t-values exceeded 1.96 (t > 1.96), and the model’s statistical indices satisfied the criteria for unidimensionality and goodness of fit. According to the Rasch analysis, all items demonstrated good fit and a high Cronbach’s alpha reliability index. A newly developed family resilience measure for Indonesian populations demonstrates strong construct validity across all dimensions and items, including a unique dimension that recognises the role of religion in family coping. While promising for clinical and research use, further validation and cross-cultural studies are needed to address limitations related to purposive sampling and cultural specificity. These studies should employ longitudinal and cross-cultural designs to enhance generalizability. This will ensure that the instrument provides a robust measure of family resilience for diverse applications. Meanwhile, the limitation of the study is the need to conduct a standardised norming of the instrument.